Gender- and age-dependencies of oxidative stress, as detected based on the steady state concentrations of different biomarkers in the MARK-AGE study - Ilya Pinchuk; Daniela Weber; Bastian Kochlik; Wolfgang Stuetz; Olivier Toussaint; Florence Debacq‐Chainiaux; Martijn E.T. Dollé; Eugène Jansen; Efstathios S. Gonos; Ewa Sikora; Nicolle Breusing; Daniela Grădinaru; et al. (2019)
Recently, Weber et al. published a thorough investigation of the age-dependency of oxidative stress (OS) determined by the steady state concentrations of different compounds - oxidation products and antioxidants - that are in common use as biomarkers of OS in 2207 healthy individuals of the cross-sectional MARK-AGE Project. The correlations among biomarkers were significant but weak. These findings may indicate different manifestations of OS and must further be evaluated. Here, we report a refined analysis of OS based on the above-mentioned original data. We show that malondialdehyde (MDA) appears to be sensitive to both gender and age. It is significantly lower and shows a greater age-dependence in women than in men. The age-dependency of MDA in women arises in a stepwise fashion. The age-dependent slope of the steady state concentration is maximal at the age between 50 and 55 years, indicating that it may be attributed to the change of metabolism in the post-menopause. Interestingly, total glutathione (GSH) decreased with age simultaneously with the increase in MDA. Different biomarkers yield different gender- and age-dependencies. Unlike the concentration of MDA, the concentrations of the other two oxidation products, i.e. protein carbonyls and 3-nitrotyrosine were similar in men and women and appeared to be independent of age in the healthy study population. The analyzed antioxidants exhibited different gender- and age-dependencies. In conclusion, it appears that all the biomarkers assessed here reflect different types of OS and that MDA and GSH reflect the same type of OS.